2018
DOI: 10.1002/ana.25322
|View full text |Cite
|
Sign up to set email alerts
|

Scalp electroencephalographic biomarkers in epilepsy patients with focal cortical dysplasia

Abstract: This study confirms that there are several surface EEG biomarkers significantly associated with an underlying cortical dysplasia. These biomarkers may aid in localizing suspicious brain regions and provide evidence for dysplastic brain tissue also in nonlesional patients of either histological FCD subtype. Ann Neurol 2018;84:564-575.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 42 publications
2
26
2
1
Order By: Relevance
“…Recruiting theta activity, delta slowing, or fast activity is all described ictal EEG features in patients with EE. 25 Neuroimaging MRI abnormalities have been noted in 30% of subjects with EE. Most lesions are described in the posterior temporal-centroparietal-occipital regions.…”
Section: Electroencephalographic Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Recruiting theta activity, delta slowing, or fast activity is all described ictal EEG features in patients with EE. 25 Neuroimaging MRI abnormalities have been noted in 30% of subjects with EE. Most lesions are described in the posterior temporal-centroparietal-occipital regions.…”
Section: Electroencephalographic Featuresmentioning
confidence: 99%
“…17 There are several surface EEG biomarkers associated with an underlying cortical dysplasia: rhythmic epileptiform discharges, focal fast continuous spikes/polyspikes, continuous irregular slowing, and "brushes," which could be present even in patients with a negative brain MRI. 23,25 Ictal onset could be focal or generalized, and apparently generalized ictal events could be recorded even in the group of patients with structural epilepsy. 4,6 Focal ictal changes may vary depending on the localization and nature of brain lesion or malformation.…”
Section: Electroencephalographic Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, numerous studies have investigated the electrophysiological characteristics of cortical epileptogenic tissue. A variety of cortical interictal patterns including trains of repetitive, rhythmic and periodic spikes/sharp waves, bursting epileptiform activity, “brushes,” and high‐frequency oscillations (HFOs) have been described over the few decades besides classical interictal discharges manifesting as a spike, spike, and wave or sharp wave 16,17 . Also, distinct ictal patterns of epileptic tissue were identified during seizures arising from cortical lesions 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Rácz's et al study indicated that age at epilepsy onset was younger in patients with FCD compared to those with GNTs (9). Though 18 F-FDG PET can't contribute to the differentiation of FCD and GNTs, 11 Cmethionine PET identified a significant difference between them (10). But, up to now, 11 C-methionine PET was unavailable in most hospitals worldwide.…”
Section: Introductionmentioning
confidence: 99%